2011
DOI: 10.1002/jrs.2922
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐shaping strategies for coherent anti‐Stokes Raman scattering

Abstract: The identification of large molecules in complex environments requires probing of multiple vibrational resonances rather than a single resonance. Phase-shaping the excitation pulses allows the coherent mixing of several resonances so that the presence of molecules can be inferred directly from the integrated output pulse energy. This avoids the need for the collection of spectra or multiple measurements. This article describes a particular implementation for coherent anti-Stokes Raman scattering microscopy tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…18 The spontaneous Raman signal is proportional to the imaginary part of the complex response, and therefore contains both amplitude and phase information. The complex vibrational response of a molecule is a sum of different vibrational resonances, where each vibrational resonance can be considered as a damped driven harmonic oscillator.…”
Section: -17mentioning
confidence: 99%
“…18 The spontaneous Raman signal is proportional to the imaginary part of the complex response, and therefore contains both amplitude and phase information. The complex vibrational response of a molecule is a sum of different vibrational resonances, where each vibrational resonance can be considered as a damped driven harmonic oscillator.…”
Section: -17mentioning
confidence: 99%
“…This availability of ultra-fast pulses has driven many research areas from basic physics to biological and medical research and to mechanical engineering. Spectacular results have been achieved such as extremely accurate optical frequency combs 3 , high speed gas spectroscopy 4 or coherent excitation applications in chemistry and biophotonics 5 . The technological improvements in laser systems now enable application of many of the developed techniques based on ultrafast optical pulses, but the cost of such laser systems is still fairly high.…”
Section: Introductionmentioning
confidence: 99%
“…Systems are needed to stabilize the laser operation as for example applications of stabilized frequency combs in telecommunication (clock distribution, multi-wavelength lasers for wavelength-division multiplexed systems) or in high speed gas spectroscopy 4 . In applications in biophotonics and coherent excitation such as multi-photon microscopy or CARS-microscopy 5 one requires (amplified) optical pulses of a specific intensity and phase at a given time in a specific location of a sample. Therefore not only stability is required but the amplitude and phase of each mode of the comb must be controlled to obtain the optimal optical pulse at the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, complete spectra have to be taken to make use of this advantage. In a theoretical study, van Rhijn et al [6] investigate whether the use of optimally shaped laser pulses are suitable for determining the presence of a specific molecule unambiguously. They apply a covariance matrix adaption evolution strategy to determine pulses, such that from the detection of the integrated output pulse energy of the nonlinear signal in a broadband pump and probe, and narrowband Stokes field CARS scheme molecule-specific contrast can be achieved.…”
mentioning
confidence: 99%
“…Thin films of the polymer poly(3-hexylthiophene) and blends of the soluble fullerene derivative [6,6]-phenyl C 61 -butyric acid methyl ester with poly(3-hexylthiophene) are used as samples. In the paper it can be shown that the Raman spectral information can be used to identify fullerene inclusions in these polymer/fullerene blends.…”
mentioning
confidence: 99%